The High Time and Frequency Resolution Capabilities of the Murchison Widefield Array. (2015) - Tremblay, S. E.; Ord, S. M.; Bhat, N. D. R.; Tingay, S. J.; Crosse, B.; Pallot, D.; Oronsaye, S. I.; Bernardi, G.; Bowman, J. D.; Briggs, F.; Cappallo, R. J.; Corey, B. E.; et al.
Abstract: The science cases for incorporating high time resolution capabilities into modern radio telescopes are as numerous as they are compelling. Science targets range from exotic sources such as pulsars, to our Sun, to recently detected possible extragalactic bursts of radio emission, the so-called fast radio bursts (FRBs). Originally conceived purely as an imaging telescope, the initial design of the Murchison Widefield Array (MWA) did not include the ability to access high time and frequency resolution voltage data. However, the flexibility of the MWA's software correlator allowed an off-the-shelf solution for adding this capability. This paper describes the system that records the 100 μs and 10 kHz resolution voltage data from the MWA. Example science applications, where this capability is critical, are presented, as well as accompanying commissioning results from this mode to demonstrate verification.